2007
DOI: 10.1017/s148180350001530x
|View full text |Cite
|
Sign up to set email alerts
|

Changing the process of care and practice in acute asthma in the emergency department: experience with an asthma care map in a regional hospital

Abstract: Introduction: Despite the frequency of acute asthma in the emergency department (ED) and the availability of guidelines, significant practice variation exists. Asthma care maps (ACMs) may standardize treatment. This study examined the use of an ACM to determine its effects on patient management in a regional hospital. Methods: Patients aged 2 to 65 years who presented to the ED with a primary diagnosis of acute asthma were enrolled in a prospective study that took place 5 months before (pre) and 5 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…This differs from the findings of the previously cited adult EMNet study, 8 as well as 2 of the 4 previous studies of this issue in children. 3,4,9,10 The process measures used in the adult study were the same 5 level A recommendations as in our study; the study revealed that 100% guideline concordance (in 12 level A and B measures) was associated with a 46% lower admission rate. 8 Among studies including children, 3 prepost studies, all single-site, evaluated the impact of use of an asthma guideline on the quality of ED asthma care.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This differs from the findings of the previously cited adult EMNet study, 8 as well as 2 of the 4 previous studies of this issue in children. 3,4,9,10 The process measures used in the adult study were the same 5 level A recommendations as in our study; the study revealed that 100% guideline concordance (in 12 level A and B measures) was associated with a 46% lower admission rate. 8 Among studies including children, 3 prepost studies, all single-site, evaluated the impact of use of an asthma guideline on the quality of ED asthma care.…”
Section: Discussionsupporting
confidence: 58%
“…3 An all-ages Canadian study revealed no change in admissions and revisits. 10 A fourth, multiinstitutional, Canadian study revealed that the presence of an asthma order sheet, but not the presence of an asthma guideline, was associated with a decreased revisit rate. 9 Our negative study is the first multicenter study of the association between guideline-concordant ED care and asthma outcomes in children and the first to use patient-level process measures, rather than the institution-level presence of a guideline, as the predictor of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One significant gap in acute asthma management in children that has been identified is under-prescription of systemic corticosteroids. 13,22,28 Guidelines recommend administration of systemic corticosteroids as early as possible during ED encounters for acute asthma to speed the resolution of airflow obstruction and prevent early relapse. 15,20 Compared to other hospitals in Ontario, 22 the use of systematic corticosteroids at our institution was already high in the retrospective group (i.e., pre-intervention period).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Clinical pathways can be effective means of supporting best practice for a variety of conditions and settings, including asthma. Single-centre studies have revealed variable improvements in patient outcomes, including bronchodilator use, 12 measurement of peak expiratory flow rate (PEFR), 13 systemic steroid use 13,14 and admissions. 14 A recent Ontario study of pediatric asthma management strategies reported that preprinted orders used in 26 of 152 EDs were associated with a 32% relative risk reduction of repeat ED visits within 72 hours, 15 presumably by embedding evidencebased medicine into clinical practice.…”
Section: Introductionmentioning
confidence: 99%